Las estratégias promocionales en el posicionamiento de la imprenta Reflex de la ciudad de Riobamba - Dario Javier, Inca Urquizo (2021)
ABSTRACT The present research work was carried out at Reflex printing company deals with promotional strategies and the impact they have on the positioning of the company; the printing company is dedicated to graphic printing and book sales in the Riobamba Canton. In the first part of the research, topics such as the introduction have been addressed, the problems faced by the SLR Printing Company have been analyzed as well as the current situation of the same. After that, specific and additional objectives were formulated, the situation of the art, which is made up of the antecedents and the theoretical foundation; were addressed within these 3 which are: • Unit 1: The generalities of the company are explained. • Unit 2: The components of promotional strategies are analyzed. • Unit 3: Positioning and its strategies. • Unit 4: Promotional strategies in positioning. Finally, the methodology was carried out through a hypothetical deductive method, the research carried out for the printing press was field and descriptive, as well as the design of the research, was non-experimental, within the population, the number of clients was considered invoiced by the printing press in 2019, with the sample of 176 people, in addition, the techniques and data collection were used, such as the survey of both internal and external customers and the interview with the manager and accountant of the company, after that, it was processed the information using the statistical software SPSS Statistics with which the analysis, discussion of results and hypothesis testing were performed. And as the last step for this investigation, the conclusions and recommendations were raised. Keywords: promotional strategies, positioning, costs, vision, environment, leadership, internal clients, external clients. Reviewed by: Dra. Nelly Moreano Ojeda ENGLISH PROFESSOR c.c. 180180728